O uso do software Calc para o ensino de gráficos estatísticos na EJA - Cardoso, Márcia Maria (2021)
The search for new teaching methods is not recent and the use of technologies and innovation has been effective in the educational context in recent decades. Therefore, this work aims to present a didactic sequence using the textit Software Calc, which can be used in classes for teaching statistics based on the creation and organization of data and the construction of graphics for students of Education Youth and Adults - EJA. The methodology used in this research consists of a literature review followed by the development of practical activities using textit Software Calc. The teaching and learning process of graphics is of paramount importance due to the wide variety of statistical texts that circulate in our environment. The use of the computer and textit Software Calc allows (in a more interesting way) the construction of tables as well as their graphics, thus contributing to the development of activities. This work contributes with a didactic material that represents the union of technological education associated with formal education and can contribute to the reflection and analysis of everyday statistics.